Risk of cardiac arrhythmias in patients with chronic hepatitis B and C infections – A 13-year nationwide population-based study. Issue 4 (October 2019) - Wu, Victor Chien-Chia; Chen, Tien-Hsing; Wu, Michael; Huang, Chien-Hao; Chen, Shao-Wei; Cheng, Chun-Wen; Lin, Yu-Sheng; Chang, Po-Cheng; Hsieh, Ming-Jer; Wang, Chao-Yung; Chang, Shang-Hung; Wang, Chun-Li; et al.
Highlights: Viral infections have been linked to atherosclerosis and arrhythmia. Hepatitis C virus (HCV) infection had higher cardiovascular events compared to hepatitis B virus (HBV). In this population study, arrhythmias in HCV and HBV patients were compared. Atrial fibrillation and sick sinus syndrome were higher in HCV patients. Cardiac arrhythmia related all-cause mortality was higher in HCV patients. Abstract: Background: Chronic hepatitis C virus (HCV) infection is associated with higher risk of cardiovascular events than chronic hepatitis B virus (HBV). We aimed to investigate whether there is higher risk of arrhythmia in HCV infection. Methods: Electronic medical records from National Health Institute Research Database during 2000–2012 were retrieved for patients with HBV or HCV. Patients with missing information, aged <18 years, diagnosed with HBV or HCV before year 2000, concomitant HBV and HCV, coagulopathy or organ transplant, history of arrhythmia, device implantation, congenital heart disease, rheumatic heart disease, hypertrophic cardiomyopathy, thyroid disease, alcohol or drug abuse, valvular heart disease, or follow-up <6 months were excluded. Primary outcomes were cardiac arrhythmias and all-cause mortality. Results: After 1:1 propensity score matching, 5480 patients with HBV and 5480 patients with HCV were included for study. During a mean follow-up of 6.5 years, the risk of all-cause mortality was higher in the HCV patients than in HBV patients [hazard ratio (HR) 1.35, 95% confidence interval (CI) 1.16–1.58]. There was also a trend toward higher incidence of atrial fibrillation (HR 1.25, 95% 0.98–1.59, p = 0.070) and a significantly higher incidence of sick sinus syndrome (HR 1.77, 95% CI 1.07–2.91) in HCV patients. In addition, among patients with all-cause mortality, arrhythmia death was significantly higher with chronic HCV infection. Conclusions: In patients with chronic viral hepatitis, patients with HCV were associated with significantly increased risks of sick sinus syndrome, and all-cause mortality compared to patients with HBV.